Inhibition of autophagy protects against sepsis by concurrently attenuating the cytokine storm and vascular leakage. Issue 3 (March 2019) - Lu, Liang-Hsuan; Chao, Chiao-Hsuan; Yeh, Trai-Ming
Highlights: Autophagy inhibition blocks the cytokine storm and vascular leakage that occur during sepsis. Autophagy inhibition promotes the uptake and clearance of E. coli by leukocytes. Hydroxychloroquine (HCQ) treatment protects E. coli -infected mice from lethality. However, pretreatment of mice with HCQ before infection causes opposite outcome. Summary: Objectives: Sepsis is an overwhelming systemic inflammatory response for which no satisfactory therapeutic drug is available. Previous studies have shown that autophagy is involved in the cytokine storm and vascular leakage that occur during sepsis. Therefore, we aimed to evaluate the therapeutic potential of autophagy inhibitors against bacterial infection-induced sepsis. Methods: Cytokine production and phagocytosis of bacteria by human leukocytes and the permeability of endothelial cells were determined after the co-incubation of cells with lipopolysaccharide (LPS) or Escherichia coli in the presence or absence of autophagy inhibitors in vitro . Furthermore, the therapeutic effects of the autophagy inhibitors in E. coli -infected mice were analysed. Results: In the presence of the autophagy inhibitors, the LPS-triggered cytokine secretion of human leucocytes and LPS (or LPS-conditioned medium from leucocytes)-induced endothelial hyperpermeability were significantly reduced. Moreover, the inhibition of autophagy enhanced the clearance of E. coli by leucocytes in vitro . Finally, we demonstrated that post-treatment but not pretreatment with an autophagy inhibitor (hydroxychloroquine) completely protected mice against E. coli infection-induced lethality by simultaneously reducing cytokine production and vascular leakage and enhancing bacterial clearance. Conclusions: These results suggest that autophagy plays an important role in the pathogenesis of sepsis and could serve as a potential therapeutic target for sepsis.